Physical and microbiological health of soil under wastewater irrigation in tuberose (Polianthes tuberosa) - GURJAR, D S; SINGH, R; KAUR, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted to find out the short term impact of wastewater irrigation on physical and microbiological soil health in tuberose (Polianthes tuberosa L. cv. Prajwal) at Water Technology Centre farm of ICAR-Indian Agricultural Research Institute, New Delhi during three consecutive seasons of 2013-14, 2014-15 and 2015-16. Seven treatments were T-1; Wastewater irrigation at 0.6 irrigation depth (ID)/ cumulative pan evaporation (CPE); T-2, Wastewater irrigation at 0.8 ID/CPE; T-3, Wastewater irrigation at 1.0 ID/CPE; T-4, Wastewater irrigation at 1.2 ID/CPE; T-5, Wastewater irrigation at 1.4 ID/CPE; T-6, Conjunctive use of groundwater and wastewater irrigation at 1.0 ID/CPE in cyclic mode; T-7, Control groundwater irrigation at 1.0 ID/CPE in randomized block design with three replications. Results indicated that soil physical properties such as bulk density, saturated hydraulic conductivity and porosity at both the soil depths of 0-15 and 15-30 cm in tuberose were significantly not changed due to application of wastewater irrigations scheduled at various ID/CPE. Significantly higher population density of fecal coliform bacteria was observed in treatment plot where wastewater irrigations were applied at 1.4 ID/CPE as compared to groundwater irrigations applied at 1.0 ID/CPE under all soil sampling dates, viz. 30, 60, 90 and 120 days after planting of tuberose bulbs.